(untitled) (Development Service Industry Management, 2025)
The article substantiates the need to form an integrated mechanism for managing the development of rural areas in Ukraine in the context of war, post-war recovery, demographic crisis, spatial imbalances, and climate risks. It shows that the current development of rural areas goes beyond purely agricultural policy and is becoming systematically important for national security, spatial cohesion, food stability, and European integration. It is emphasized that the existing resource and human potential of rural areas is combined with deep structural problems that cannot be overcome by fragmented or sector-oriented instruments of state support. The study summarizes contemporary scientific approaches to the sustainable and integrated development of rural areas, identifies their methodological and institutional fragmentation, and demonstrates the feasibility of transitioning to a comprehensive management model. It proposes an interpretation of the integrated mechanism for managing the development of rural areas as a systematically organized complex of institutions, entities, instruments, and procedures that ensure the coordination of economic, social, spatial, environmental, security, and institutional decisions with a focus on improving the quality of life of the population. The structural logic of the integrated mechanism is revealed, covering diagnostic and analytical, economic and financial, institutional and organizational, spatial and infrastructural, socio-demographic, digital, and security and environmental subsystems. The role of program-targeted and project-based approaches, multi-level governance, public-private partnerships, and digitalization as key conditions for the effective implementation of an integrated rural development policy is substantiated. It has been proven that the proposed mechanism creates a methodological basis for adaptive management of rural areas, strengthening the sustainability of communities, and forming long-term trajectories of spatial development of Ukraine in accordance with European standards.